INTEGRATION OF STORYTELLING AND ECOLOGICAL AWARENESS IN RUSKIN BOND’S SHORT STORIES - Karunya, R. Margaret (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Literature has always been the testimony of human-nature relationships. Without nature, human existence is inconceivable. Owing to the emergence of Industrial Revolution and modern technology, the harmonious relationship between human and nature has been deformed. Man has started to exploit nature. Humankind is currently dealing with a serious environmental crisis on Earth. Ruskin Bond has remained a true love of nature throughout his life. His stories examine and observe the symbiotic relationship between nature and humans. This paper aims to investigate the ecological consciousness of Ruskin Bond’s short stories like the interdependent relationship between nature and human, accountability of human towards the environment.